Experimental study on flexural behavior of bonded steel-concrete composite beams - Junhu Shao; Haijun Jiang; Lei Zhang; Wenfeng Huang; Tingmin Mou; Yuehan Sun (Scientific Reports)
Abstract To address the limitations of mechanical shear connectors, adhesives are used in this research as shear connectors of steel-concrete composite beams (SCCBs). Several groups of bending tests were conducted to compare the flexural behavior of bonded and mechanical SCCBs. Moreover, the results show that the failure modes of the bonded SCCBs mainly include yielding of the bottom flange of the I-beam and the cracking of the concrete bottom surface, local detachment between the two bonding surfaces and the crushing of the concrete slab at the top surface. The rigidity of the bonded SCCB is higher than that of the mechanical one. In addition, the ultimate load of the bonded SCCB connected by 6 mm thick epoxy resin is the highest, which is about 16.8% higher than that of mechanical one. Furthermore, increasing the adhesive layer’s thickness can improve the adhesive performance to a certain extent. Thus, it is suggested that the adhesive thickness should exceed 4 mm, and 6 mm is the optimal. In addition, as local detachment of the adhesive layer occurred in this test, further research can be carried out to avoid such damage.